PETA KAJIAN ATAS NOVEL SEJARAH ISLAM KARYA JURJĪ ZAIDĀN - Moh. Wakhid Hidayat, Sangidu, Fadlil Munawwar Manshur, Taufiq Ahmad Dardiri (CMES (Center of Middle Eastern Studies), 2019)
The novel of Islamic history by Jurjī Zaidān is one of the works of Modern Arabic literature which appeared at the end of the 19th century. Since it was first published, as a serial story in al-Hilal magazine, this novel has been read and has received a great response. Zaidān composed 22 titles of novels from 1891 to 1914. After Zaidān's death in 1914, his novels were still read by the public, reprinted, and even translated in various languages in the world. Zaidān’s Islamic historical novels still exist, both within the scope of modern Arabic literature and in Arabic thought, with many studies to date. Research on this novel is reviewed and analyzed to reveal the diversity of perspectives to be mapped. Found nine perspectives in the study of Islamic historical novels; the perspective of the development of Arabic novel genres, the perspective of authorship and pioneering in Arabic novel genre, the perspective of the popularization of Arab-Islamic history, critical perspectives of Islamic historical facts, intrinsic literary criticism perspective, narrative structure perspective, feminist perspective, perspective modern Arab identity, and Arab nationalism perspective. The mapping of studies become the positioning of further Islamic historical novel studies, and at the same time can be a model of study for the analysis of other historical novels that develop in Arabic literature or other national literature.